2010
DOI: 10.1101/gr.100370.109
|View full text |Cite
|
Sign up to set email alerts
|

Sequence features that drive human promoter function and tissue specificity

Abstract: Promoters are important regulatory elements that contain the necessary sequence features for cells to initiate transcription. To functionally characterize a large set of human promoters, we measured the transcriptional activities of 4575 putative promoters across eight cell lines using transient transfection reporter assays. In parallel, we measured gene expression in the same cell lines and observed a significant correlation between promoter activity and endogenous gene expression (r = 0.43). As transient tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 39 publications
10
79
0
Order By: Relevance
“…There are two main differences between this work and our study reported here. First, as pointed out by Landolin et al (2010), the promoters are not in their endogenous context in the plasmid. Therefore, this effort reflects the role that sequence plays in determining expression outside of the chromatin context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two main differences between this work and our study reported here. First, as pointed out by Landolin et al (2010), the promoters are not in their endogenous context in the plasmid. Therefore, this effort reflects the role that sequence plays in determining expression outside of the chromatin context.…”
Section: Discussionmentioning
confidence: 99%
“…A related recent study monitored expression using transient transfection assays for several promoters (Landolin et al 2010). The investigators then used sequence features in the transfected plasmids to predict expression with high accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively short core-binding motifs of TFs can appear numerous times in a genome, but only a very small fraction of these putative binding sites is functional (Landolin et al 2010;Spitz and Furlong 2012). TFs can precisely identify their functional binding sites from among the other 99.8% of putative binding sites in a cellular environment in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, experimental advances have enabled characterization of the binding motifs for hundreds of TFs in vitro (5)(6)(7)(8)(9), mapping of the genome-wide binding sites of TFs in vivo (10)(11)(12)(13)(14), and functional characterization of the enhancer activity of thousands of genomic sequences (15)(16)(17)(18)(19). Comparisons between these experiments, however, have revealed that only a small fraction of the potential TF-binding sites (TFBSs) in eukaryotic genomes are actually occupied by TFs in any given cell type, and that these sites vary substantially across cell types and conditions (3,(19)(20)(21). Moreover, only a subset (∼25-50%) of bound TFBSs can drive transcription in reporter assays (17)(18)(19)22).…”
mentioning
confidence: 99%